Restricted nature of adult neural stem cells: re-evaluation of their potential for brain repair - Obernier, Kirsten; Tong, Cheuk Ka; Alvarez-Buylla, Arturo (Frontiers in Neuroscience, 2014)
Neural stem cells (NSCs) in the walls of the lateral ventricles continue to produce new neurons and oligodendrocytes throughout life. The identification of NSCs, long-range neuronal migration, and the integration of new neurons into fully formed mature neural circuits -- all in the juvenile or adult brain -- has dramatically changed concepts in neurodevelopment and suggests new strategies for brain repair. Yet, the latter has to be seen in perspective: NSCs in the adult are heterogeneous and highly regionally specified; young neurons derived from these primary progenitors migrate and integrate in specific brain regions. Neurogenesis appears to have a function in brain plasticity rather than brain repair. If similar processes could be induced in regions of the brain that are normally not a target of new neurons, therapeutic neuronal replacement may one day reinstate neural circuit plasticity and possibly repair broken neural circuits.